2010
DOI: 10.1063/1.3407561
|View full text |Cite
|
Sign up to set email alerts
|

Hole transport in the organic small molecule material α-NPD: evidence for the presence of correlated disorder

Abstract: In this paper the hole mobility in the amorphous small molecule material N,NЈ-bis͑1-naphthyl͒-N,NЈ-diphenyl-1 , 1Ј-biphenyl-4 , 4Ј-diamine ͑␣-NPD͒, which is frequently used in organic light-emitting diodes, is studied. From an analysis of the temperature and layer thickness dependence of the steady-state current density in sandwich-type ␣-NPD-based hole-only devices, it is found that a conventional mobility model assuming a Poole-Frenkel type field dependence and neglecting the carrier density dependence is no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
55
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 75 publications
6
55
0
Order By: Relevance
“…In this model, the value C = 0.25 is obtained. The simulated values of σ were 0.130 eV (α-NPD) and 0.227 eV (Alq 3 ), with the former value close to the EGDM value found in the modeling of α-NPD devices [12], but incompatible with the ECDM value. The GEMM prediction of the T dependence of the mobilities was found to agree rather well with experiment, even at low T .…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…In this model, the value C = 0.25 is obtained. The simulated values of σ were 0.130 eV (α-NPD) and 0.227 eV (Alq 3 ), with the former value close to the EGDM value found in the modeling of α-NPD devices [12], but incompatible with the ECDM value. The GEMM prediction of the T dependence of the mobilities was found to agree rather well with experiment, even at low T .…”
Section: Introductionmentioning
confidence: 70%
“…The c dependence of both models was shown to be essentially the same [11]. Good agreement between measured T -dependent current density-voltage (J -V ) characteristics of hole-only devices of α-NPD [N,N -Di(1-naphthyl)-N,N -diphenyl-(1, 1 -biphenyl)-4,4 -diamine] and those calculated with both the EGDM and ECDM could be obtained, but with different values of σ and N t : σ = 0.14 eV, N t = 0.20 × 10 27 m −3 for the EGDM and σ = 0.10 eV, N t = 3.7 × 10 27 m −3 for the ECDM [12]. Because for the ECDM N t was closer to the actual density of molecules than for the EGDM, it was suggested that site energies in α-NPD are spatially correlated.…”
Section: Introductionmentioning
confidence: 98%
“…On the other hand, a similar comparison of EGDM and ECDM modeling of current-voltage characteristics of hole-only devices of the molecule N,N -bis(1-naphthyl)-N,N -diphenyl-1,1 -biphenyl-4,4 -diamine (α-NPD) and of electron-only devices of the molecule bis(2-methyl-8-quinolinolato)(4-phenylphenolato) aluminum (BAlq) shows that the intersite distance as obtained from a fit with the ECDM modeling is more realistic than the one obtained with the EGDM modeling. 12,13 This work suggests that for the investigated polymers and small-molecule semiconductors the EGDM and the ECDM, respectively, are thus the best models to describe charge transport.…”
Section: Introductionmentioning
confidence: 99%
“…22,23 This model has been applied to describe the charge carrier mobility measured in an organic sandwich-type diode device. [23][24][25] Note that the electric field in such diode devices is normally much larger than the lateral electric field in an OFET due to very different interelectrode distances.…”
Section: Introductionmentioning
confidence: 99%